(untitled) (Ameghiniana, 2013)
Resumen. En esta contribución se describe una nueva especie de Stegotheriini (Xenarthra, Dasypodidae), Stegotheriumtauberi, a base de materiales previamente asignados a Stegotheriumtessellatum Ameghino y otros recientemente descubiertos. Todos los materiales provienen de afloramientos de la Formación Santa Cruz (Edad Santacrucense, Mioceno temprano tardío) ubicados entre los estuarios de los ríos Coyle y Gallegos (provincia de Santa Cruz, Argentina). Los materiales reasignados son los restos más completos para la tribu Stegotheriini. Asimismo, Stegotherium tauberi es el Stegotheriini de distribución más austral conocido. Abstract. A NEW SPECIES OF STEGOTHERIUM AMEGHINO (XENARTHRA, DASYPODIDAE, STEGOTHERIINI) FROM THE MIOCENE OF SANTA CRUZ PROVINCE (ARGENTINA). A new species of Stegotheriini (Xenarthra, Dasypodidae), Stegotheriumtauberi is described here based on materials previously attributed to Stegotheriumtessellatum Ameghino, as well as additional specimens discovered recently. All the specimens came from outcrops of the Santa Cruz Formation (Santacrucian Age, late early Miocene) located between the estuaries of the rivers Coyle and Gallegos (Santa Cruz Province, Argentina). The materials reassigned here represent the most complete for the tribe Stegotheriini. Moreover, Stegotheriumtauberi is the southernmost Stegotheriini discovered up to now.